Bunching at 3 Percent : The Maastricht Fiscal Criterion and Government Deficits - Caselli, Francesca (IMF Working Papers; Working Paper ;, 2018)
This paper estimates the effects of the Maastricht treaty's fiscal criterion on EU countries' general government deficits. We combine treatment effects methods with bunching estimation, and find that the 3 percent deficit rule acts as a 'magnet', increasing the number of observations around the threshold, while reducing the occurrence of both large government deficits and surpluses. After the rule is adopted, the distribution of government deficits among EU countries displays 20 percent excess mass around the deficit ceiling compared to a counterfactual distribution in which countries have the same observable characteristics but without the fiscal rule. Most of the bunching response comes from a reduction in the number of high deficit observations. We also find that the average treatment effect on fiscal deficits is positive and statistically significant. Finally, we derive country-specific impacts under a rank invariance assumption and find that all EU countries have seen their fiscal position improve on average as a result of the deficit rule.